Advances in Porous Semiconductor Research - Djenizian, Thierry; Hans Voelcker, Nicolas (Frontiers Media SA, 2020)
Since the discovery of the luminescent properties of porous Si by L. Canham in 1990, the anodization process has attracted enormous interest for the fabrication of porous semiconductors. To date, this technique has been widely used to design new materials with advanced physico-chemical properties for many applications in optics, microelectronics, energy, biology and medicine.